Modified positive electrode material and preparation method thereof, and secondary battery
By mixing the polymer PDP and boric acid obtained by the dione and dihamine reactions for high -temperature insulation treatment, porous composite materials are formed, and wet ball milling with the positive pole material solves the lattice of the traditional lithium -ion batteries. The problem of collapse significantly improves the cycle stability and energy density of the battery.
Patent Information
- Application Number
- CN202411321240.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The phase transition of the positive electrode material of traditional lithium-ion batteries when charged to a high level causes the lattice to collapse, hindering the rapid transmission of lithium ions, resulting in a decrease in electrode capacity and shortening battery life.
By mixing the polymer PDP and boric acid obtained by the dione and dihamine reactions for high -temperature insulation treatment, the porous composite material is obtained, and the wet ball grinding with the positive pole material is used to form a modified positive pole material.
The rate performance, cycle stability and structural stability of the modified cathode material are significantly improved, extending the cycle life of the battery and increasing the energy density.
Smart Images

Figure CN118877957B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery cathode material technology, specifically relating to the modification of cathode materials. Background Technology
[0002] Lithium-ion batteries are widely used in digital products, new energy electric vehicles, and electrical energy storage. With the accelerating pace of electrification in the energy and transportation sectors, traditional cathode materials can no longer meet the demand for high-energy-density batteries, necessitating the development of novel composite cathode materials with higher energy density and longer cycle life. Traditional cathode materials experience phase transitions and lattice collapse when charged to high levels, hindering the rapid transport of lithium ions within the electrode, leading to decreased electrode capacity and shortened battery life.
[0003] Cathode materials are one of the key components of lithium-ion batteries, directly affecting their overall performance, such as capacity and cycle life. Currently, most multilayered metal oxides have low electronic conductivity, resulting in low actual specific capacity, poor cycle performance, and unsatisfactory capacity retention in their cathodes. Achieving high-capacity reversibility is relatively difficult. Therefore, modification is necessary to overcome this trade-off by reducing structural degradation and volume changes without compromising high capacity. The most common and effective modification methods include coating and doping. Summary of the Invention
[0004] This application provides modified cathode materials and their preparation methods, as well as secondary batteries.
[0005] To achieve the above objectives, this application proposes the following technical solution:
[0006] Firstly, a method for preparing modified cathode materials is provided, including:
[0007] S1. Diketones and diamines are dissolved in an organic solvent and reacted under the action of a catalyst to obtain a polymer PDP containing both ester and amino groups.
[0008] S2. The polymer PDP is mixed with boric acid and then kept at 700~900℃ under a protective atmosphere to obtain the product. The product is then filtered, washed and dried to obtain a porous composite material.
[0009] S3. The cathode material and the porous composite material are wet ball-milled, then subjected to solid-liquid separation and drying to obtain the modified cathode material.
[0010] Further, the diketone is one or more selected from 2,5-dimethoxyacyl-1,4-cyclohexanedione, 2,5-diethyl ester-1,4-cyclohexanedione, and 2,5-bis(1-methylethyl ester)-1,4-cyclohexanedione.
[0011] Further, the diamine is one or more of p-phenylenediamine, 2,6-diaminonaphthalene, and 2,6-diaminoanthracene.
[0012] Furthermore, the catalyst is one or more of p-toluenesulfonamide, triethylamine p-methylsulfonate, and tetrabutyl p-toluenesulfonate.
[0013] Furthermore, the organic solvent is one or more of alcohols and chlorobenzene solvents.
[0014] Furthermore, the molar ratio of the diketone to the diamine is 1:1 to 1:1.2.
[0015] Furthermore, the amount of the catalyst used is 1.5 mol% to 2.0 mol% of the diketone.
[0016] Furthermore, in step S1, the reaction temperature is 100~140℃; the reaction time is 40~72h.
[0017] Further, in step S2, the weight ratio of the polymer PDP to boric acid is 1:1 to 1:1.2.
[0018] Furthermore, in step S2, the heat preservation treatment time is 2~5 hours.
[0019] Furthermore, in step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
[0020] Furthermore, in step S2, the mixing is ball milling mixing.
[0021] Further, in step S3, the porous composite material is 2 to 10 wt.% of the mass of the modified cathode material.
[0022] Furthermore, the cathode material is one or more of the following: lithium-ion battery layered cathode material, sodium-ion battery layered cathode material, spinel lithium manganese oxide, lithium iron phosphate, sodium iron phosphate, and lithium cobalt oxide.
[0023] Furthermore, the chemical formula of the layered cathode material for the lithium-ion battery is LiNi. x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3 and x+y+z=1.
[0024] Furthermore, the chemical formula of the layered cathode material for the sodium-ion battery is NaNi. x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3 and x+y+z=1.
[0025] Furthermore, in step S3, the solvent used in the wet ball milling is one or more of pure water, n-hexane, methanol, acetone, DMF, and NMP.
[0026] Furthermore, in step S3, the wet ball milling time is 2-5 hours.
[0027] Secondly, a modified cathode material is provided, which is prepared using the aforementioned preparation method.
[0028] Thirdly, a secondary battery is provided, comprising the aforementioned modified cathode material.
[0029] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0030] Polymer PDP is obtained by reacting diketone with diamine. Then, the polymer PDP is mixed with boric acid and subjected to high-temperature heat preservation treatment to obtain a porous composite material. The porous composite material is then coated on the surface of the cathode material to obtain a modified cathode material. The rate performance, cycle stability and structural stability of the cathode material modified by coating with the porous composite material are significantly improved. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 The infrared spectrum of polymer A prepared in step (1) of Example 1 is shown.
[0033] Figure 2 The image shows the SEM image of the composite material prepared in step (1) of Example 1.
[0034] Figure 3 XPS image of the composite material prepared in step (1) of Example 1.
[0035] Figure 4 The image shows the SEM image of the cathode material precursor prepared in step (5) of Example 1.
[0036] Figure 5 The image shows the SEM image of the cathode material prepared in step (6) of Example 1.
[0037] Figure 6 The cyclic voltammetry curves are for the battery assembled with the modified cathode material prepared in Example 2. Detailed Implementation
[0038] This invention provides a method for preparing a modified cathode material, comprising:
[0039] S1. Diketones and diamines are dissolved in an organic solvent and reacted under the action of a catalyst to obtain a polymer PDP containing both ester and amino groups.
[0040] S2. After mixing the polymer PDP with boric acid, the mixture is kept at 700~900℃ under a protective atmosphere to obtain the product. The product is then filtered, washed and dried to obtain a porous composite material.
[0041] S3. The cathode material and the porous composite material are wet ball-milled, then subjected to solid-liquid separation and drying to obtain the modified cathode material.
[0042] In some preferred embodiments, the diketone is one or more of 2,5-dimethoxyyl-1,4-cyclohexanedione, 2,5-diethyl-1,4-cyclohexanedione, and 2,5-bis(1-methylethyl)-1,4-cyclohexanedione. It is worth noting that although the diketone used in the example embodiment is 2,5-dimethoxyyl-1,4-cyclohexanedione, 2,5-diethyl-1,4-cyclohexanedione and 2,5-bis(1-methylethyl)-1,4-cyclohexanedione can also be used as substitutes to achieve a similar effect.
[0043] In some preferred embodiments, the diamine is one or more of p-phenylenediamine, 2,6-diaminonaphthalene, and 2,6-diaminoanthracene. It is worth noting that although p-phenylenediamine is used as the diamine in the example embodiment, 2,6-diaminonaphthalene and 2,6-diaminoanthracene can also be used as substitutes to achieve a similar effect.
[0044] In some preferred embodiments, the catalyst is one or more of p-toluenesulfonamide, triethylamine p-methanesulfonate, and tetrabutyl p-toluenesulfonate. It is worth noting that although the example embodiment uses p-toluenesulfonamide as the catalyst, ethylamine p-methanesulfonate and tetrabutyl p-toluenesulfonate can also be used as catalysts for the polymerization of diamines and diketones.
[0045] In some preferred embodiments, the organic solvent is one or more of alcohols and chlorobenzene solvents, more preferably a mixed solvent of n-butanol and o-dichlorobenzene; even more preferably, the volume ratio of n-butanol to o-dichlorobenzene is 1:1.05 to 1:2.
[0046] In some preferred embodiments, the molar ratio of the diketone to the diamine is 1:1 to 1:1.2, such as 1:1, 1:1.02, 1:1.05, 1:1.08, 1:1.1, 1:1.12, 1:1.15, 1:1.18, 1:1.2, etc.
[0047] In some preferred embodiments, the amount of catalyst used is 1.5 mol% to 2.0 mol% of the diketone, for example, 1.5 mol%, 1.6 mol%, 1.7 mol%, 1.8 mol%, 1.9 mol%, 2.0 mol%, etc.
[0048] In some preferred embodiments, the amount of organic solvent can be conventionally determined based on the solubility of the raw materials, and its function is to dissolve the raw materials.
[0049] In some preferred embodiments, in step S1, the reaction temperature is 100~140℃, for example 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, etc.; the reaction time is 40~72h, for example 40h, 45h, 50h, 55h, 60h, 65h, 70h, 72h, etc.
[0050] In some preferred embodiments, in step S2, the weight ratio of the polymer PDP to boric acid is 1:1 to 1:1.2, for example, 1:1, 1:1.02, 1:1.05, 1:1.08, 1:1.1, 1:1.12, 1:1.15, 1:1.18, 1:1.2, etc.
[0051] In some preferred embodiments, in step S2, the heat preservation treatment time is 2 to 5 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, etc.
[0052] In step S2, the protective atmosphere can be a conventional protective atmosphere in the art, such as a nitrogen atmosphere or an inert gas atmosphere (e.g., argon, helium, or other inert gas atmospheres).
[0053] In step S2, the mixing can be carried out using any existing method that can achieve uniform mixing of the two substances. In some embodiments, the mixing can be ball milling or grinding.
[0054] In some preferred embodiments, in step S3, the porous composite material is 2 to 10 wt.% of the mass of the modified cathode material, for example, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, etc.
[0055] Although the modified substrate of the modified cathode material described in each embodiment is a layered cathode material for lithium-ion batteries, this modification scheme is also applicable to other cathode materials. It is worth noting that the modified substrate can be a conventional cathode material for lithium-ion or sodium-ion batteries; for example, the cathode material can be one or more of sodium-ion battery layered cathode materials, lithium-ion battery layered cathode materials, spinel lithium manganese oxide, lithium iron phosphate, sodium iron phosphate, and lithium cobalt oxide. These cathode materials can undergo conventional doping modifications in the art. The chemical formula of the sodium-ion battery layered cathode material can be NaNi. x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3, and x+y+z=1. The chemical formula of the layered cathode material for the lithium-ion battery can be LiNi. x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3, and x+y+z=1.
[0056] It is worth noting that in the above preparation method, the cathode material can be prepared using conventional preparation methods in the art, such as solid-state sintering, solvent gelation, spray drying, etc. When the cathode material is a layered cathode material for sodium-ion batteries or a layered cathode material for lithium-ion batteries, a hydroxide or carbonate precursor can also be prepared by co-precipitation, and then sintered with a sodium source or lithium source.
[0057] In some embodiments, the modified matrix of the example modified cathode material is a layered cathode material for lithium-ion batteries, which is prepared using a conventional co-precipitation method to obtain a spherical or near-spherical hydroxide precursor Ni. x Co y Mn zThe precursor material is (OH)₂, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3, and x+y+z=1. The median particle size D50 of the precursor material is 3~4μm. The precursor material is then mixed with a lithium source and sintered to obtain a layered cathode material for sodium-ion batteries. The lithium source can be one or more of the conventional lithium sources used in the preparation of layered cathode materials for lithium-ion batteries, such as lithium hydroxide monohydrate, lithium acetate, lithium carbonate, and lithium sulfate. The amount of lithium source can also be the amount commonly used in the preparation of layered cathode materials for lithium-ion batteries; specifically, the molar ratio of lithium in the precursor to lithium in the lithium source can be 1:1.02~1.05. The sintering mechanism can also adopt conventional sintering methods and process parameters in the art, with a sintering temperature of 650~950℃, a heating rate of 5~10℃ / min, and a calcination time of 10~24h; the sintering atmosphere can be conventional sintering atmospheres in the art, such as an oxygen atmosphere or an air atmosphere.
[0058] In some embodiments, in step S3, the solvent used for wet ball milling can be one or more of pure water, n-hexane, methanol, acetone, DMF, and NMP.
[0059] In some embodiments, in step S3, the wet ball milling time is 2-5 hours and the ball mill speed is 300-400 rpm.
[0060] The present invention also provides a modified cathode material, which is prepared by the aforementioned preparation method. The modified cathode material includes a cathode material matrix and a coating material located on at least a portion of the surface of the cathode material matrix. The coating material is a composite material of porous carbon compound and boric acid.
[0061] The present invention also provides a secondary battery, which can be a lithium-ion battery or a sodium-ion battery, including the aforementioned modified cathode material.
[0062] To facilitate understanding of the present invention, the invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0063] Example 1
[0064] The preparation method of the modified cathode material includes the following steps:
[0065] (1) Dissolve 7.0 g of 2,5-dimethoxyacyl-1,4-cyclohexanedione and 3.5 g of p-phenylenediamine completely in o-dichlorobenzene (10 mL) and n-butanol (10 mL), transfer the solution to a polymerization sleeve, add 100 mg of p-toluenesulfonamide catalyst, sonicate for 3-5 min, and then transfer the solution to 120 °C for two days. After the reaction is complete, filter and wash to remove impurities, leaving the solid. Dry the solid to obtain the polymer product. The infrared spectrum of the polymer is shown below. Figure 1 As shown in the infrared spectrum, at 3370 cm⁻¹ -1 The strong characteristic peak is attributed to the amino group of the diamine monomer, 1260 cm⁻¹. -1 The characteristic peak at 1630 cm⁻¹ belongs to the CN group in the diamine monomer; the diketone peak at 1630 cm⁻¹ belongs to the CN group in the diamine monomer. -1 It exhibits the characteristic absorption peak of a carbonyl group; after polymerization of the two monomers, the peak is at 3320 cm⁻¹. -1 The nearby characteristic peak is attributed to imino groups, 1240 cm⁻¹. -1 and 1200cm -1 The characteristic peaks at the point of origin belong to the COC group of the polymer, indicating that the polymer has been successfully synthesized. The polymer is prepared by polymerization of diamine monomers and diketones. Based on the English names of the raw materials, the polymer is named PDP polymer. Subsequently, the PDP polymer and boric acid (weight ratio 1:1.05) were ground and mixed evenly, then placed in a ceramic boat and transferred to a tube furnace under a nitrogen atmosphere. The temperature was increased to 800℃ at a rate of 5℃ / min and reacted under constant temperature conditions for 3 hours. Boric acid acted as an activator, dopant, and crosslinking agent during this process. The activator effect resulted in a larger specific surface area, providing channels for subsequent ion transport. The dopant effect provided a source of boron. The crosslinking agent effect occurred during the reaction, where intermolecular hydrogen bonds formed between the oxygen in the carbonyl group and the hydroxyl group in the boric acid, and another oxygen in the ester group formed an N…O bond with the N in the imino group, locking the B and N elements within the carbon chain framework. After the reaction, the product was filtered and washed five times with deionized water. The filter cake was dried and dehydrated in a vacuum oven at 120℃ for 12 hours to obtain the composite material. Its SEM image is shown below. Figure 2 As shown, from Figure 2 It can be seen that the composite material is a porous material; the obtained XPS full spectrum of the porous composite material is as follows. Figure 3 As shown in Table 1, the percentage content of B- / N- substances in the porous composite material is as follows.
[0066] Table 1
[0067]
[0068] Combination Figure 3 As shown in Table 1, the full-scan spectrum exhibits four distinct peaks: B 1s at 190.5 eV, C 1s at 286.1 eV, N 1s at 399.8 eV, and O 1s at 531.0 eV. This indicates that the material is mainly composed of four elements: B, C, N, and O. It confirms that element B was successfully embedded in the carbon chain backbone, and the source of element B is boric acid. During the reaction, due to the intermolecular hydrogen bonds, elements B and N are locked in the carbon chain backbone.
[0069] (2) Add the sulfates of nickel, cobalt and manganese in a molar ratio of 70:10:20 to pure water to prepare a ternary metal salt solution with a concentration of 120 g / L;
[0070] (3) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0071] (4) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while 6mol / L sodium hydroxide solution and 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5~4μm, and then the reaction is stopped.
[0072] (5) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is (Ni 0.70 Co 0.10 Mn 0.20 (OH)2, its SEM image is as follows Figure 4 As shown;
[0073] (6) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.70 Co 0.10 Mn 0.20 O2, its SEM image is as follows Figure 5 As shown.
[0074] (7) Take 98g of nickel cobalt manganese cathode material and 2g of porous composite material prepared in step (1) and place them in a ball mill. Add 3~5ml of LDMF and mix by wet ball milling. After ball milling for 3 hours, filter the mixture and vacuum dry the filter cake to obtain porous composite material coated modified cathode material, wherein the porous composite material accounts for 2wt.% of the coated modified cathode material.
[0075] Example 2
[0076] The preparation method of the modified cathode material includes the following steps:
[0077] (1) 2,5-Dimethoxyacyl-1,4-cyclohexanedione (7.0 g) and p-phenylenediamine (3.5 g) were completely dissolved in o-dichlorobenzene (10 mL) and n-butanol (10 mL), and transferred to a polymerization sleeve. Then, p-toluenesulfonamide (100 mg) was added as a catalyst. After sonication for 3-5 min, the mixture was transferred to 120 °C and reacted for two days. After the reaction was completed, the mixture was filtered and washed to remove impurities, leaving a solid. After drying, the product PDP polymer was obtained. Subsequently, the PDP polymer and boric acid (weight ratio 1:1.05) were ground and mixed evenly and placed in a ceramic boat. Under a nitrogen atmosphere, the mixture was transferred to a tube furnace and heated to 800 °C at a heating rate of 5 °C / min. The mixture was reacted under constant temperature conditions for 3 h. After the reaction was completed, the product was filtered and washed 5 times with deionized water. The filter cake was dried and dehydrated in a vacuum oven at 120 °C for 12 h to obtain a porous composite material mainly containing B, N, C, and O.
[0078] (2) Add nickel, cobalt and manganese sulfates to pure water at a molar ratio of 75:10:15 to prepare a ternary metal salt solution with a concentration of 120 g / L.
[0079] (3) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0080] (4) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while 6mol / L sodium hydroxide solution and 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5~4μm, and then the reaction is stopped.
[0081] (5) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is: (Ni 0.75 Co 0.10 Mn 0.15 (OH)2;
[0082] (6) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.75 Co0.10 Mn 0.15 )]O2.
[0083] (7) Take nickel-cobalt-manganese cathode material (95g) and porous composite material (5g) and place them in a ball mill. Add 3~5ml of LDMF and mix by wet ball milling. After ball milling for 3 hours, filter and vacuum dry the filter cake layer to obtain porous composite material coated modified cathode material, wherein the porous composite material accounts for 5wt.% of the coated modified cathode material.
[0084] Example 3
[0085] The preparation method of the modified cathode material includes the following steps:
[0086] (1) 2,5-Dimethoxyacyl-1,4-cyclohexanedione (7.0 g) and p-phenylenediamine (3.5 g) were completely dissolved in o-dichlorobenzene (10 mL) and n-butanol (10 mL), and transferred to a polymerization sleeve. Then, p-toluenesulfonamide (100 mg) was added as a catalyst. After sonication for 3-5 min, the mixture was transferred to 120 °C and reacted for two days. After the reaction was completed, the mixture was filtered and washed to remove impurities, leaving a solid. After drying, the product PDP polymer was obtained. Subsequently, the PDP polymer and boric acid (weight ratio 1:1.05) were ground and mixed evenly and placed in a ceramic boat. Under a nitrogen atmosphere, the mixture was transferred to a tube furnace and heated to 800 °C at a heating rate of 5 °C / min. The mixture was reacted under constant temperature conditions for 3 h. After the reaction was completed, the product was filtered and washed 5 times with deionized water. The filter cake was dried and dehydrated in a vacuum oven at 120 °C for 12 h to obtain a porous composite material mainly containing B, C, N, and O.
[0087] (2) Add nickel, cobalt and manganese sulfates to pure water at a molar ratio of 80:5:15 to prepare a ternary metal salt solution with a concentration of 120 g / L.
[0088] (3) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0089] (4) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while 6mol / L sodium hydroxide solution and 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5~4μm, and then the reaction is stopped.
[0090] (5) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is: (Ni 0.80 Co 0.05 Mn 0.15 (OH)2;
[0091] (6) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.80 Co 0.05 Mn 0.15 )]O2.
[0092] (7) Take 92g of nickel cobalt manganese cathode material and 8g of porous composite material obtained in step (5) and place them in a ball mill. Add 3-5ml of LDMF and mix by wet ball milling. After ball milling for 3 hours, filter the mixture and vacuum dry the filter cake to obtain porous composite material coated modified cathode material, wherein the porous composite material accounts for 8wt.% of the coated modified cathode material.
[0093] Comparative Example 1
[0094] The only difference between this comparative example and Example 1 is that no coating modification was performed, and the preparation method specifically includes:
[0095] (1) Add nickel, cobalt and manganese sulfates to pure water at a molar ratio of 70:10:20 to prepare a ternary metal salt solution with a concentration of 120 g / L;
[0096] (2) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0097] (3) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while a 6mol / L sodium hydroxide solution and a 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5~4μm, and then the reaction is stopped.
[0098] (4) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is: (Ni 0.70 Co 0.10 Mn 0.20 (OH)2;
[0099] (5) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.70 Co 0.10 Mn 0.20 )]O2.
[0100] Comparative Example 2
[0101] The only difference between this comparative example and Example 2 is that no coating modification was performed. The preparation method specifically includes:
[0102] (1) Add nickel, cobalt and manganese sulfates to pure water at a molar ratio of 75:10:15 to prepare a ternary metal salt solution with a concentration of 120 g / L.
[0103] (2) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0104] (3) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while a 6mol / L sodium hydroxide solution and a 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5~4μm, and then the reaction is stopped.
[0105] (4) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is: (Ni 0.75 Co 0.10 Mn 0.15 (OH)2;
[0106] (5) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.75 Co 0.10 Mn 0.15 )]O2.
[0107] Comparative Example 3
[0108] The only difference between this comparative example and Example 3 is that no coating modification was performed. The preparation method specifically includes:
[0109] (1) Add nickel, cobalt and manganese sulfates to pure water at a molar ratio of 80:5:15 to prepare a ternary metal salt solution with a concentration of 120 g / L.
[0110] (2) Take 350 mL of 6 mol / L sodium hydroxide solution and 4.2 L of 4 mol / L ammonia solution, mix them into 60 L of pure water as the reaction base liquid, stir thoroughly and put them into a 100 L reaction vessel, heat and raise the temperature to stabilize the reaction vessel temperature at 60 °C.
[0111] (3) At a stirring rate of 800~1000r / min, the ternary metal salt solution is pumped into the reactor at a flow rate of 1~3L / h, while 6mol / L sodium hydroxide solution and 4mol / L ammonia solution are simultaneously introduced. The pH value and ammonia concentration of the reaction system in the reactor are adjusted in real time to be in the range of 11.0~12.0 and 5~6g / L, respectively. The reaction time is maintained between 110~120h until the median particle size D50 of the precipitated particles reaches 3.5-4μm, and then the reaction is stopped.
[0112] (4) Separate the precipitate, rinse with hot pure water at 60℃ for 5-6 hours, centrifuge and dry, then transfer to an oven at 130℃ to dry for 12-15 hours. Subsequently, sieve through a 300-mesh vibrating screen to obtain the nickel-cobalt-manganese ternary precursor, whose chemical formula is: (Ni 0.80 Co 0.05 Mn 0.15 (OH)2;
[0113] (5) The nickel-cobalt-manganese ternary precursor and lithium hydroxide monohydrate were thoroughly mixed at a molar ratio of 1:1.05. The mixture was heated to 850°C in a muffle furnace at a heating rate of 10°C / min and calcined for 18 hours under a constant temperature and pure oxygen atmosphere. After naturally cooling to room temperature, the mixture was pulverized and sieved to obtain a layered oxide cathode material with the chemical formula Li[(Ni 0.80 Co 0.05 Mn 0.15 )]O2.
[0114] The layered oxide cathode materials prepared in Examples 1-3 and Comparative Examples 1-3 were assembled into coin-type lithium-ion batteries. The specific process is as follows: 24 mg of cathode material, 3 mg of acetylene black, and 3 mg of polyvinylidene chloride (PVDF) were weighed and added to a 25 mL weighing bottle. 10-12 drops of N-methyl-2-pyrrolidone (NMP) were added and mixed evenly. After sonication for 20 minutes, the mixture was stirred for 3 hours to obtain a homogeneous black slurry. Subsequently, the slurry was coated onto copper foil using an automatic coating machine, and then dried at 120°C under vacuum for 8 hours to remove the solvent. Finally, it was pressed at 16 MPa using a tablet press to obtain the cathode sheet. The active material loading on each individual working electrode was approximately 3.0 mg / cm³. 2 Using a positive electrode sheet as the positive electrode and a lithium sheet as the negative electrode, the electrolyte consisted of EC+DMC (molar ratio 1:1.2) as the solvent, with a LiPF6 concentration of 1 mol / L. A microporous polyethylene separator was assembled into a 2032-type coin cell in an argon-atmospheric glove box. The coin cells were then transferred to a 25°C constant temperature chamber and subjected to constant current charge-discharge testing on a Blue Battery testing system. The voltage range was 2.7~4.5V. The electrodes were first activated by two cycles at 0.1C, followed by 200 cycles at 0.5C. The initial charge-discharge capacity, the discharge capacity at 0.5C, and the capacity retention after 200 cycles at 0.5C are shown in Table 1.
[0115] Table 1:
[0116]
[0117] Table 1 shows that, compared with the corresponding comparative examples of batteries assembled from composite cathode materials prepared with coating modification in each embodiment, the batteries assembled from cathode materials prepared without coating modification exhibit higher coin capacity, with a first-cycle discharge specific capacity as high as 261 mAh / g and a capacity retention rate of up to 88% after 200 cycles at a current density of 0.5C. This demonstrates that the discharge specific capacity and cycle performance of the modified cathode materials are significantly improved. Analysis suggests this may be due to: 1. The porous composite material forms a core-shell structure with the internal nickel-cobalt-manganese matrix material. The coating layer of the porous composite material effectively alleviates the volume expansion caused by charging and discharging, reduces side reactions between the electrolyte and the cathode material, and improves the stability of the electrode material; 2. Due to the covalent bonding of the porous composite material molecules, a porous conductive network is formed, increasing the electrochemical active area and promoting electron transport and ion migration within the electrode. Therefore, the electrode material can possess high capacity, good cycle stability, and rate performance.
[0118] The cyclic voltammetry curve of the coin cell assembled from the cathode material prepared in Example 2 is shown below. Figure 6As shown. Due to the presence of the porous carbon polymer coating, electrode activation is relatively slow, resulting in a weak redox peak in the first CV curve. As the test progresses, Li... + As the material is continuously activated and becomes free within the crystal framework, the conductivity of the electrode is further improved, hence the enhanced redox peak in the second CV curve. The redox peak in the third curve is basically consistent with that in the second curve, indicating that the conductivity of the electrode is stable. The high overlap between the redox peaks in the second and third curves means that the potential value of the material is stable during charging or discharging, indicating that the prepared cathode material has good reversibility during charging and discharging, demonstrating that the material has good electrochemical stability.
[0119] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified positive electrode material, characterized in that: include: S1. Dissolve a diketone and a diamine in an organic solvent, react under the action of a catalyst, and obtain a polymer PDP containing both an ester group and an amino group; the diketone is one or two of 2,5-dimethoxyacyl-1,4-cyclohexanedione and 2,5-diethylester-1,4-cyclohexanedione; the diamine is one or more of p-phenylenediamine, 2,6-diaminonaphthalene, and 2,6-diaminoanthracene; the catalyst is one or more of p-toluenesulfonamide and tetrabutyl p-toluenesulfonic acid ammonium; the reaction temperature is 100-140°C; S2, mixing the polymer PDP with boric acid, and heat-treating the mixture at 700-900° C. under a protective atmosphere to obtain a product, and filtering, washing and drying the product to obtain a porous composite material; S3. The positive electrode material and the porous composite material are subjected to wet ball milling, followed by solid-liquid separation and drying to obtain a modified positive electrode material.
2. The method for preparing the modified positive electrode material according to claim 1, characterized in that: The organic solvent is one or more of alcohol and chlorobenzene solvents.
3. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: The molar ratio of the diketone to the diamine is 1:1 to 1:1.2; The amount of the catalyst used is 1.5 mol% to 2.0 mol% of the diketone.
4. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: In step S1, the reaction time is 40 to 72 hours.
5. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: In step S2, the weight ratio of the polymer PDP to boric acid is 1:1 to 1:1.
2.
6. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: In step S2, the heat preservation treatment time is 2 to 5 hours; In step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere; In step S2, the mixing is ball milling mixing.
7. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: In step S3, the porous composite material is 2-10wt.% of the mass of the modified positive electrode material; The positive electrode material is one or more of a lithium ion battery layered positive electrode material, a sodium ion battery layered positive electrode material, spinel lithium manganese oxide, lithium iron phosphate, sodium iron phosphate, and lithium cobalt oxide; The chemical formula of the lithium-ion battery layered positive electrode material is LiNi x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3 and x+y+z=1; The chemical formula of the sodium ion battery layered cathode material is NaNi x Co y Mn z O2, where 0.7≤x≤0.8, 0≤y≤0.1, 0.1≤z≤0.3 and x+y+z=1.
8. The method for preparing a modified positive electrode material according to claim 1 or 2, characterized in that: In step S3, the solvent used for the wet ball milling is one or more of pure water, n-hexane, methanol, acetone, DMF and NMP; In step S3, the wet ball milling time is 2 to 5 hours.
9. A modified positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Includes the modified positive electrode material as described in claim 9.
Citation Information
Patent Citations
Method for preparing porous carbon coated nickel-doped lithium cobalt oxide composite anode material
CN104393287A
Nitrogen-boron co-doped carbon quantum dot coated nickel cobalt lithium aluminate battery cathode material and preparation method
CN110098394A